2014
DOI: 10.1111/ajo.12254
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal management of at‐risk pregnancies from a distance

Abstract: This study was undertaken to determine whether antenatal care can be achieved in women with at-risk pregnancies residing in rural areas with limited access to antenatal care and maternal fetal medicine (MFM) specialists. Over a period of 15 months, 156 women with high-risk pregnancies (diabetes, hypertensive disorders, suspected fetal anomalies, prior caesarean complications) from six different healthcare units had 350 visits managed by telemedicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 8 publications
0
18
1
Order By: Relevance
“…This is higher than the study done by Ivy et al where 27.5% referrals were done and in study by Lund et al where 10% of referrals were done in interventional group and 5% in control group. 17,16 In the present study, 101 women out of 102 in study group (one woman aborted at 12 weeks) and 102 in control group had institutional deliveries which were high when compared to study done by Battle et al where 75% delivered at a facility and 78% delivered under skilled care. 18 In our study, a significant difference was noted in Hb% in last visit in study group [p-0.004] when compared to a study done by Khorshid et al where no effect on anaemia was found, as there were no significant differences in hemoglobin and hematocrit in study group.…”
Section: Discussioncontrasting
confidence: 55%
“…This is higher than the study done by Ivy et al where 27.5% referrals were done and in study by Lund et al where 10% of referrals were done in interventional group and 5% in control group. 17,16 In the present study, 101 women out of 102 in study group (one woman aborted at 12 weeks) and 102 in control group had institutional deliveries which were high when compared to study done by Battle et al where 75% delivered at a facility and 78% delivered under skilled care. 18 In our study, a significant difference was noted in Hb% in last visit in study group [p-0.004] when compared to a study done by Khorshid et al where no effect on anaemia was found, as there were no significant differences in hemoglobin and hematocrit in study group.…”
Section: Discussioncontrasting
confidence: 55%
“…However, the question remains as to whether Internet-based interventions may offer cost-effective service compared to usual care [28]. Interventions delivered over the Internet are likely to cost less than face-to-face services requiring frequent contact with health care personnel, and their relatively low delivery cost could result in an Internet-based intervention being more cost effective [4,26].…”
Section: Discussionmentioning
confidence: 99%
“…Four reviews focused on the use of technologies to evaluate healthy pregnant women in terms of maternal outcomes [27], women with complicated pregnancies in terms of cost effectiveness [28], a mixed group of patients (with type 1 DM and GDM) in terms of maternal-neonatal outcomes [29], and patients with GDM in terms of maternal outcomes [30]. These studies reported mixed results, did not include ongoing studies without outcomes [27], lacked systematic searching strategies [28,29], and evaluated limited studies (n=3) [30]. None of the studies focused on Internet-based self-monitoring approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Antenatal management of high-risk pregnancies from a distance has been accomplished for conditions ranging from maternal diabetes, hypertensive disorders, cervical insufficiency, and suspected fetal anomalies, including congenital heart disease (90)(91)(92). In Arkansas, telemedicine-supported care in the rural setting has been shown to reduce the need for in-person visits (where the mother would have to travel to the tertiary center) by nearly 50%, while maintaining the appropriate utilization of maternal-fetal medicine subspecialty consultations (91).…”
Section: Perinatal and Newborn Carementioning
confidence: 99%